If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8+19s-2=6s+54-3s
We move all terms to the left:
8+19s-2-(6s+54-3s)=0
We add all the numbers together, and all the variables
19s-(3s+54)+8-2=0
We add all the numbers together, and all the variables
19s-(3s+54)+6=0
We get rid of parentheses
19s-3s-54+6=0
We add all the numbers together, and all the variables
16s-48=0
We move all terms containing s to the left, all other terms to the right
16s=48
s=48/16
s=3
| 3+k/3=-3 | | 180=3x-5+x+1 | | 2.9+9.2x=5.2 | | 4x+6=10x+3=59 | | 16h=2000-400 | | -8(5x+7)=-336 | | 8-4x-3=-6x+9 | | -29=3+2m | | 6x+13=10x+53 | | b^2+5b-3=-7 | | -5(4x-2=-2(3+6x | | 2.30+0.60x=27.3-0.40x | | -5×y/3+3=8 | | x/5+3x/4=19 | | 5+3/4x=x-6 | | 4(1+6p)−8=−148 | | 2.9+10m=8.72 | | t3− 13=–10 | | 11x-26=x-4x-16+9x | | -8.5x=17 | | 5(x-)-8=22 | | 3x=24-2 | | 4x^2-17x-10=5 | | 30-2t=4t | | 5x–9=4x+7+x | | -46=-4+3m | | 7x+28=8x+2) | | ?x15=105 | | -12=2-5x=7 | | 4=x^2-6 | | -(3x-3)-(2x-5)+4=-5(x1)-(3x+2)+3 | | -11+11n=-121 |